Evaluation of Patterns of Presentation, Practice, and Outcomes of Upper Tract Urothelial Cancer: Protocol for an Observational, International, Multicenter, Cohort Study by the Clinical Research Office of the Endourology Society - Baard, Joyce; Celebi, Merve; de la Rosette, Jean; Alcaraz, Antonio; Shariat, Shahrokh; Cormio, Luigi; Cavadas, Vítor; Laguna, M Pilar (JMIR research protocols, 2020)
BACKGROUND: Available guidelines on the management of upper tract urothelial carcinoma (UTUC) are restricted due to the lack of strong evidence-based recommendations. Adequate, well-powered randomized trials are missing due to the rarity of the disease. To overcome this problem, we need alternative study designs to provide generalizable data. OBJECTIVE: The primary aim of this registry is to provide a real-world overview on patterns of presentation and management of UTUC. Secondary objectives include comparison of outcomes of different treatments and tumor stages and evaluation of compliance with the current European Association of Urology recommendations for UTUC. METHODS: For this observational, international, multicenter, cohort study, clinical data of consecutive patients suspected of having UTUC, irrespective of type of management, will be prospectively collected up to 5 years after inclusion. Data on the patterns of presentation, diagnostics, and treatment as well as short-, mid-, and long-term oncological and functional outcomes will be analyzed. Possible associations between variables, basal characteristics, and outcomes will be tested by multivariable analyses. The methodology will address potential sources of bias and confounders. RESULTS: The registry was initiated in November 2014 after obtaining institutional review board approval. Data collection started in December 2014. At the time of submission of this manuscript, 2451 patients from 125 centers from 37 countries were included. Inclusion of patients will be closed 5 years after initiation of the registry. Quality checks will be performed centrally with continuous communication and feedback with the centers to ensure accuracy. The first results are expected in the first trimester of 2020. CONCLUSIONS: This large observational prospective cohort will generate landmark "real-world" data and hypotheses for further studies. We expect these data to optimize the management of UTUC, provide insights on harms and benefits of treatment, and serve as quality control. TRIAL REGISTRATION: ClinicalTrials.gov NCT02281188; https://clinicaltrials.gov/ct2/show/NCT02281188. INTERNATIONAL REGISTERED REPORT IDENTIFIER (IRRID): DERR1-10.2196/15363.
Keywords: urothelial cancer; management; registry; outcomes; incidence; upper urinary tract